The Development TASC-based Classical Guidance through Work Culture to Enhance Vocational Students' Work Readiness - Ratmi Kuswati; Suwarjo Suwarjo (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to develop a classical guidance model based on work culture, "Thinking Actively in a Social Context" (TASC), to improve the work readiness of vocational high school students (SMK). This study also tests the feasibility, practicality, and effectiveness of the model. The implementation of the classical guidance model based on work culture, TASC, is intended to improve the work readiness of SMK students. This study uses a Research and Development (R&D) model with a 4D model. The subjects of the study included students of SMK Negeri 2 Pengasih and guidance and counseling teachers at vocational high schools in Kulon Progo Regency. Data were collected through questionnaires and pretest-posttest tests, which were then analyzed quantitatively. The results of the study indicate that the classical guidance model, TASC, is feasible, practical, and effective. A large group trial with 30 students showed an increase in work readiness scores from an average of 64.47 (pretest) to 82.73 (posttest), with an N-Gain of 0.52 (moderate category). In conclusion, the classical guidance model based on work culture, TASC, has been proven to be feasible, practical, and effective in improving the work readiness of vocational high school students. The final product, the TASC guidance model based on work culture, can be used as an innovation in classical guidance services to facilitate the strengthening of work culture in vocational high schools.